IMPLEMENTATION OF TELEDENTISTRY IN PREVENTING DENTAL AND ORAL DISEASES IN INDONESIA: THE APPLICATION OF TELEDENTISTRY IN EFFORTS TO PREVENT DENTAL AND ORAL DISEASES IN INDONESIA - Wicaksono, Muhammad Syarif; Arsanti, Meilan; Hartanto, Hamdan Ali (JURNAL TERAS KESEHATAN, 2024)
The prevalence of dental and oral diseases in Indonesia is still high. Data from the Riset Kesehatan Dasar (Riskesdas) 2018 shows that dental and oral health problems in Indonesia are 57.6%. Prevention of dental and oral diseases needs to be disseminated from the lowest levels such as individuals, families, to the community. Teledentistry is an innovation that can be useful for reaching people who have difficulty with accessibility. The aim of this research is to determine the application of teledentistry in preventing dental and oral diseases in Indonesia. The method used in this research is the literature review. The results of this research are that teledentistry can be used to prevent dental and oral disease and promote dental and oral health. The teledentistry method most often used to prevent dental and oral disease is the store and forward (asynchronous) method.